IMPLEMENTASI METODE SMART DAN TOPSIS DALAM SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JUARA DUTA BAHASA PROVINSI ACEH - Mustafa, M. Rafli Al Thoriq; Ulfa, Chairina; Chairunnisa , Indah (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
This research implements the SMART and TOPSIS methods in a decision support system for determining the champion of Aceh Province Language Ambassador 2025. The system was developed to improve time efficiency in judging by utilizing quantitative data from 20 finalists consisting of 10 participants in the Cut Bang category and 10 participants in the Cut Kak category. The analysis showed high consistency between the two methods, with X5 ranked first and X8 ranked second in the Cut Bang category. Meanwhile, Y4 obtained the highest position in the Cut Kak category. The maximum ranking difference only reached three positions. This reflects the stability of the system. The Final Honor (15%) and Language (12%) criteria proved to be the dominant factors in determining the results. The SMART method excels in simplicity and ease of interpretation, while TOPSIS provides a sharper separation of scores between finalists. A combination of both methods is recommended as cross-validation to improve accuracy. The developed web-based system allows easy access by stakeholders with transparent and structured documentation of the calculation process.